Concept of Social Entrepreneurship Values in Pesantren Based on the Success Story of a Religious Social Entrepreneur - Furqonul Haq (Mabny: Journal of Sharia Management and Business, 2025)
This study explores the core values and operational mechanisms of religious social entrepreneurship through the case of Sholah Al Athiyah in Tafahna Al Asyrof, Egypt. This research utilizes a qualitative approach through document analysis of biographical records of Sholah Al Athiyah's business journey. Based on the success story of Sholah Al Athiyah, the concept of social entrepreneurship values ​​in Islamic boarding schools consists of three elements. First, spiritual values: the "Divine Partnership" framework. Second, social values: holistic empowerment and poverty alleviation. Finally, institutional values: infrastructure and scale. This framework provides a scalable model for Pesantren economic independence and community vocational empowerment. There has never been a study on social entrepreneurship concept in pesantren which inspired religious muslim entrepreneur